Welcome to Cal Poly (1977)
[00:00:11] Introduction music [00:00:21] 'Welcome to Cal Poly' title screen [00:00:32] Shot of cars driving onto campus [00:00:42] Administration shots of buildings and faculty [00:00:58] Various shots of Agriculture Department; includes agriculture mechanics, food processing, rodeo practice, veterinary clinic, livestock [00:03:53] Architecture Department [00:04:51] Various shots of the Dexter Library [00:05:46] Various shots of Sports teams on campus [00:06:15] Shots of students teaching children [00:06:39] English Department [00:07:00] Cal Poly Arts: Theater, Marching Band, printing [00:08:06] Engineering Department [00:10:58] Various shots of campus and student life [00:11:56] Credits